Shear Forces from Flow Are Responsible for a Distinct Statistical Signature of Adherent Microbubbles in Large Vessels - Shiying Wang; F. William Mauldin; Alexander L. Klibanov; John A. Hossack (Molecular Imaging)
Real-time ultrasound-based targeted molecular imaging in large blood vessels holds promise for early detection and diagnosis of stroke risk by identifying early markers for atherosclerosis prior to plaque formation. Singular spectrum-based targeted molecular (SiSTM) imaging is a recently proposed method that uses changes in statistical dimensionality—quantified by a normalized singular spectrum area (NSSA)—to image receptor-ligand–bound adherent microbubbles. However, the precise physical mechanism responsible for the distinct statistical signature was previously unknown. In this study, in vitro flow phantom experiments were performed to elucidate the physical mechanism in large blood vessel environments. In the absence of flow, an increase in the NSSA of adherent microbubbles with respect to tissue was not observed with increased microbubble concentration or pulse length ( p > .23; n = 5) but was observed with increased flow rate ( p < .01; n = 10). When observing the dynamics of the adherent microbubble statistics, a good correlation was observed between the NSSA and the derivative of image intensity ( R 2 > .97). In addition, a monotonic relationship between the NSSA and decorrelation was demonstrated. These findings confirm the hypothesis that the statistical signature of adherent microbubbles is derived from frame-to-frame decorrelation, which is induced by flow shear forces.